2014
DOI: 10.1093/icesjms/fsu181
|View full text |Cite
|
Sign up to set email alerts
|

Longline hook testing in the mouths of pelagic odontocetes

Abstract: Several species of odontocete cetaceans depredate bait and catch and, as a result, become hooked and entangled in pelagic longline fisheries. The present study measured how selected commercial longline hooks, including “weak hooks”, behaved within odontocete mouths. Five hooks (Mustad-16/0, Mustad-18/0, Mustad J-9/0, Korean 16, and Korean 18) were tested on three species of odontocetes known to interact with longline fisheries—short-finned pilot whales (Globicephala macrorhynchus), Risso's dolphins (Grampus gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Modifications to longlines have been extensively trialed. Hook modifications (McLellan et al, 2015;Hamilton and Baker, 2019), gangions (O'Connell et al, 2015) and decoys (Wild et al, 2017), have (commercial and small-scale fisheries); as per the management categories described by Dawson et al (2013). significantly reduced the rate of killer whale and sperm whale depredation in longline gear.…”
Section: Technological Interventions To Change the Nature Of Interact...mentioning
confidence: 99%
“…Modifications to longlines have been extensively trialed. Hook modifications (McLellan et al, 2015;Hamilton and Baker, 2019), gangions (O'Connell et al, 2015) and decoys (Wild et al, 2017), have (commercial and small-scale fisheries); as per the management categories described by Dawson et al (2013). significantly reduced the rate of killer whale and sperm whale depredation in longline gear.…”
Section: Technological Interventions To Change the Nature Of Interact...mentioning
confidence: 99%
“…Baird et al (2014) proposed that trailing edge fin scars could potentially occur if whales that became hooked in the mouth thrashed or twisted against the line to break free. Given the low probability of observing beaked whale entanglements, simulation of entanglement mechanics occurring with lines and gear associated with offshore fisheries (e.g., McLellan et al, 2015;Howle et al, 2018) could provide insight on the origin of other unusual scars. Additional analysis of melon and beaks photographs, or aerial imagery of the entire body (e.g., Ramp et al, 2021) would provide another perspective on patterns observed here and comparative estimates of the rate of fisheries interactions.…”
Section: Implications Of Anthropogenic Interactionsmentioning
confidence: 99%
“…Gear modification is an available and common mitigation approach in the absence of assessment (see below). For example, much research has focused on modifying longline gear to reduce the likelihood that animals get hooked (e.g., Bigelow et al, 2012;McLellan et al, 2015).…”
Section: Mitigating Marine Mammal Bycatchmentioning
confidence: 99%